Hepatic gas gangrene caused by Clostridium novyi. (June 2019) - Watanabe, Noriyuki; Kobayashi, Kiyoko; Hashikita, Giichi; Taji, Yoshitada; Ishibashi, Noriomi; Sakuramoto, Shinichi; Mitsutake, Kotaro; Ikebuchi, Kenji; Ebihara, Yasuhiro
Abstract: We report the case of a patient with advanced gastric cancer and multiple liver metastases, who presented with bacteremia and hepatic gas gangrene caused by Clostridium novyi ( C. novyi ). The gas gangrene caused abscesses to form within metastatic lesions. This case highlights the antitumor effects of C. novyi in human. Highlights: The patient with gastric cancer and hepatic metastasis had hepatic gas gangrene. Hepatic gas gangrene was caused by C. novyi. The metastatic lesions were converted to abscesses by gas gangrene. This phenomenon supported the antitumor effects of C. novyi in human.